Rsf-1 expression in rectal cancer: with special emphasis on the independent prognostic value after neoadjuvant chemoradiation. Issue 8 (8th May 2012) - Lin, Ching-Yih; Tian, Yu-Feng; Wu, Li-Ching; Chen, Li-Tzong; Lin, Li-Ching; Hsing, Chung-Hsi; Lee, Sung-Wei; Sheu, Ming-Jen; Lee, Hao-Hsien; Wang, Yu-Hui; Shiue, Yow-Ling; Wu, Wen-Ren; et al.
Abstract : Aims: Neoadjuvant chemoradiation therapy (CRT) is an increasingly used therapeutic strategy for rectal cancer. Clinically, it remains a major challenge to predict therapeutic response and patient outcome after CRT. Rsf-1 (HBXAP), a novel nuclear protein with histone chaperon function, mediates ATPase-dependent chromatin remodelling and confers tumour aggressiveness and predicts therapeutic response in certain carcinomas. However, the expression of Rsf-1 has never been reported in rectal cancer. This study examined the predictive and prognostic impacts of Rsf-1 expression in patients with rectal cancer following neoadjuvant CRT. Methods: Rsf-1 immunoexpression was retrospectively assessed for pre-treatment biopsies of 172 rectal cancer patients without initial distant metastasis. All of them were treated with neoadjuvant CRT followed by surgery. The results were correlated with the clinicopathological features, therapeutic response, tumour regression grade and metastasis-free survival (MeFS), local recurrent-free survival and disease-specific survival. Results: Present in 82 cases (47.7%), high-expression of Rsf-1 was associated with advanced pre-treatment tumour status (T3, T4, p=0.020), advanced post-treatment tumour status (T3, T4, p<0.001) and inferior tumour regression grade (p=0.028). Of note, high-expression of Rsf-1 emerged as an adverse prognosticator for diseases-specific survival (p=0.0092) and significantly predicted worse MeFS (p=0.0006). Moreover, high-expression of Rsf-1 also remained prognostic independent for worse MeFS (HR 2.834; p=0.0214). Conclusions: High-expression of Rsf-1 is associated with poor therapeutic response and adverse outcome in rectal cancer patients treated with neoadjuvant CRT, which confers tumour aggressiveness and therapeutic resistance through chromatin remodelling and represents a potential prognostic biomarker in rectal cancer.